2022
DOI: 10.2500/aap.2022.43.220014
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging therapies for eosinophilic esophagitis

Abstract: Background: Eosinophilic esophagitis (EoE) is a Type-2 chronic inflammatory food antigen‐driven disease of the esophagus, characterized by eosinophilic predominant inflammation and a constellation of symptoms. The incidence and prevalence of EoE has increased over the past 2 decades. There is an unmet need for approved less burdensome treatment options. Objective: To describe the underlying pathophysiology and diagnosis of EoE and discuss the currently available treatment options. We also aim to review the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Unfortunately, being the most comfortable for the patient does not mean that it will guarantee the greatest effectiveness. Studies have shown that for the above-mentioned diets, the highest remission was achieved when six components are eliminated in 50–71% of patients [ 4 , 77 ]. In the case of the diets excluding four and two components, remission was achieved in 46–54 and 43–44% of cases, respectively [ 10 , 77 ].…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, being the most comfortable for the patient does not mean that it will guarantee the greatest effectiveness. Studies have shown that for the above-mentioned diets, the highest remission was achieved when six components are eliminated in 50–71% of patients [ 4 , 77 ]. In the case of the diets excluding four and two components, remission was achieved in 46–54 and 43–44% of cases, respectively [ 10 , 77 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Studies have shown that for the above-mentioned diets, the highest remission was achieved when six components are eliminated in 50–71% of patients [ 4 , 77 ]. In the case of the diets excluding four and two components, remission was achieved in 46–54 and 43–44% of cases, respectively [ 10 , 77 ]. Therefore, considering the patient’s habits, a step-up empiric approach to food elimination was proposed, beginning with the two-food elimination diet (2-FED) [ 78 ].…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations